Turner's syndrome associated with bicuspid aortic stenosis and dissecting aortic aneurysm. Issue 681 (July 1982) - Slater, D. N.; Grundman, M. J.; Mitchell, L.
Abstract : A case of Turner's syndrome is described associated with bicuspid aortic stenosis and fatal rupture of a thoracic dissecting aortic aneurysm. Histology of the aneurysm showed severe cystic medial necrosis. This association has not been previously described in the absence of coarctation. In view of the possibility of surgical repair, dissecting aortic aneurysm should be considered in all patients with Turner's syndrome presenting with chest pain, irrespective of the presence or absence of coarctation.